FUENTES DE FONDEO DE LA BANCA ECUATORIANA. - Navia Aray, Jessica Roxana (2016)
Ecuadorian Banking, it´s by nature, characterized on operating mainly with third-party resources, main sources are deposits that come from Bank's customers, in other words, it is a high regulated activity by financial entities. There is a close relationship between funding sources and usage to which they are targeted. This specific connection is important because it can be vague from the point of view of the investor, since a client can operate in more than one mode at a time or migrate from one type of investment to another, depending on a variety of factors such as passive interest rate, financial risk, among others. This individual behavior of the depositor should be perfectly managed by the financial entities, ensuring a banking spread to cover operating costs and maintain its liquidity indicators, profitability and solvency according to Local established regulations, that, to ensure depositors fund's stability and represent an attractive profit margin to shareholders. Through this thesis we pursuit to define a methodology for registration of passive operations of the Ecuadorian financial system.